Anaplasma phagocytophilum Infection in Ixodes ricinus, Bavaria, Germany - Cornelia Silaghi (Emerging Infectious Diseases, 2008)
Anaplasma phagocytophilum DNA was detected by real-time PCR, which targeted the msp2 gene, in 2.9% of questing Ixodes ricinus ticks (adults and nymphs; n = 2,862), collected systematically from selected locations in Bavaria, Germany, in 2006. Prevalence was significantly higher in urban public parks in Munich than in natural forests.